2018
DOI: 10.1002/jcp.27387
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces ZEB2 in podocytes: Implications in the pathogenesis of proteinuria

Abstract: The glomerular filtration barrier (GFB) plays a critical role in ensuing protein free urine. The integrity of the GFB is compromised during hypoxia that prevails during extreme physiological conditions. However, the mechanism by which glomerular permselectivity is compromised during hypoxia remains enigmatic. Rats exposed to hypoxia showed a decreased glomerular filtration rate, podocyte foot-processes effacement, and proteinuria. Accumulation of hypoxia-inducible factor-1α (HIF1α) in podocytes resulted in ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 52 publications
1
34
0
Order By: Relevance
“…ZEB2 expression is concomitant with HIF1α accumulation in podocytes exposed to hypoxia 22 . ZEB2, a zinc-finger transcription factor regulates the expression of several proteins representing various cellular processes including cell adhesion and epithelial-mesenchymal transition (EMT).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…ZEB2 expression is concomitant with HIF1α accumulation in podocytes exposed to hypoxia 22 . ZEB2, a zinc-finger transcription factor regulates the expression of several proteins representing various cellular processes including cell adhesion and epithelial-mesenchymal transition (EMT).…”
Section: Resultsmentioning
confidence: 98%
“…Earlier studies revealed that accumulation of HIF1α in podocytes increased podocyte permeability to albumin and blunting the expression of ZEB2 diminished the susceptibility podocyte monolayer to hypoxia-driven elevated albumin influx 22 . This data strongly suggest that ZEB2 is necessary to elicit HIF1α’s action on podocyte permeability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations